Assessments of Modal Split in Long-distance Passenger Transport - Jakub Chmelík (Review of Economic Perspectives, 2015)
The goal of this paper is to present basic alternative assessments of the division of transport work (or also “modal split”) of main transport modes. For this, an example of selected long-distance connections between centres in Czechia, including an identification of major underlying factors, shall be exploited. The paper examines the competitiveness of rail transport in its relation to bus and individual automobile transport, and relations with a potential of rail transport are primarily selected. A logit model is applied within the selected set of relations. It is entered in particular by indicators of time (time of a ride, frequency of public transport lines) and finances (actual transport costs) through a financial expression of generalised costs. The purpose of the paper is to verify the selected procedure on the relations transport modes of which are similar, and to highlight the alternatives of a comprehensive assessment of the modal split of main transport modes in Czechia. In the conclusion, the gained results are used to outline further alternative prospects of the topic under observation.
Keywords: 330